Essentials of Performance Analysis in Sport, 3rd Edition (Routledge, 2020)
The coaching process is about enhancing performance by providing feedback about the performance to the athlete or team. Researchers have shown that human observation and memory are not reliable enough to provide accurate and objective information for high-performance athletes. Objective measuring tools are necessary to enable the feedback process. These can take the form of video analysis systems post-event, both biomechanical and computerised notation systems, or the use of in-event systems.